ORGANIZING TRANSPORT SERVICES IN MOUNTAINOUS AREAS: CHALLENGES AND SOLUTIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article examines the problems of developing transport services in hard-to-reach areas of Uzbekistan, particularly in mountainous and remote regions. In the article, projects being implemented in Uzbekistan to build transport infrastructure in mountainous regions, modernize freight and passenger transport services, and ensure international connectivity are analyzed. The research methodology demonstrates the importance of developing transport services under difficult conditions, using the construction of the Tashkent–Andijan, Angren–Pop, Toshguzar–Boysun–Kumkurgan railways and the Kamchiq Tunnel as examples. The article uses digital literature to scientifically analyze problems and their solutions, and, based on this analysis, recommends the main directions for future development of the transport sector. It examines modern approaches to organizing transport services in Uzbekistan’s hard-to-reach areas, particularly mountainous regions (Kashkadarya, Surkhandarya, and the areas around the Fergana Valley) and desert regions (Karakalpakstan and the Navoi region). The research methodology results discuss the organization of Uzbekistan’s total road network of 184,000 km, the construction of the 223 km Toshguzar–Boysun–Kumkurgan railway in mountainous areas, and transport provision issues for the 18.5 million people living in rural areas.